Activation of mammalian endplate receptors by iontophoretic application of reducing and oxidizing sulphydryl reagents (Revista Española de Fisiología, 1985)
The effects of microelectrophoretic application of sulphydryl reagents at both the endplate region and extrasynaptic sites have been studied in the mouse diaphragm neuromuscular preparation.Two groups of sulphydryl reagents have been tested: oxidizing agents and reducing agents.Reagents were applied iontophoretically by means of a microelectrophoretic programmer with constant current source.Both groups of sulphydryl reagents elicit depolarizations only when applied at the endplate region.Presynaptic components were ruled out by addition of magnesium chloride to the bathing medium.After blockade of neuromuscular transmission, the depolarizing effect of both groups of sulphydryl reagents persisted.The present results suggest the presence of reactive disulphide bonds and SH groups in the receptor complex of the mammalian neuromuscular junction.These groups could be located at the alpha subunit of the acetylcholine receptor.